2008
DOI: 10.1176/jnp.2008.20.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Cerebral Dysrhythmic Abnormalities in the Trinity of Nonepileptic General Population, Neuropsychiatric, and Neurobehavioral Disorders

Abstract: Subclinical electroencephalographic epileptiform discharges in neurobehavioral disorders are not uncommon. The clinical significance and behavioral, diagnostic, and therapeutic implications of this EEG cerebral dysrhythmia have not been fully examined. Currently the only connotation for distinctive epileptiform electroencephalographic patterns is epileptic seizures. Given the prevailing dogma of not treating EEGs, these potential aberrations are either disregarded as irrelevant or are misattributed to indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 76 publications
3
33
1
Order By: Relevance
“…Further research in these conditions might improve our understanding of the meaning of unusual EEG patterns. Several studies investigating clinical EEG in psychiatric populations reported the presence of the controversial waveform (see Shelley et al [49] for a review of the literature). Small sharp spikes, 6/second spike and waves and positive bursts of 14 and 6 Hz have been reported in 20-40% of patients with mood disorders [50][51][52][53], as well as in 33% of patients with schizoaffective disorder and in 30% of patients with schizophreniform disorder [53].…”
Section: Box 46 Non-controversial Unusual Eeg Patterns (Normal Variamentioning
confidence: 99%
“…Further research in these conditions might improve our understanding of the meaning of unusual EEG patterns. Several studies investigating clinical EEG in psychiatric populations reported the presence of the controversial waveform (see Shelley et al [49] for a review of the literature). Small sharp spikes, 6/second spike and waves and positive bursts of 14 and 6 Hz have been reported in 20-40% of patients with mood disorders [50][51][52][53], as well as in 33% of patients with schizoaffective disorder and in 30% of patients with schizophreniform disorder [53].…”
Section: Box 46 Non-controversial Unusual Eeg Patterns (Normal Variamentioning
confidence: 99%
“…However: r A high percentage of patients with schizophrenia shows EEG abnormalities whose correlates are still not understood [3,4].…”
Section: Eeg In Schizophreniamentioning
confidence: 99%
“…epileptiform variants were investigated in recent studies only), which makes findings difficult to compare; the most recent studies often did not include a healthy comparison group and normative ranges of the EEG features were poorly defined [3,12].…”
Section: Eeg Findings In Schizophreniamentioning
confidence: 99%
“…Over the course of the last six decades, a voluminous literature has emerged that substantiated a high prevalence of conventional EEG findings in psychiatric populations (Shelley et al, 2008).…”
mentioning
confidence: 99%
“…A well-established fact is that the incidence of EEG abnormalities, both slow-wave abnormalities and epileptiform discharges (EDs), is higher in psychiatric populations as compared with nonneurologic control groups (Shelley et al, 2008). It should be noted that most EDs detected in nonepileptic psychiatric patients are focal in nature and tend to be recorded from the more behaviorally salient brain regions like the temporal and frontal areas (Boutros et al, 2011a).…”
mentioning
confidence: 99%